2005
DOI: 10.2174/0929867054020864
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in the Medicinal Chemistry of Cannabimimetic Indoles, Pyrroles and Indenes

Abstract: During the development of new nonsteroidal anti-inflammatory agents, it was discovered that 1-aminoalkyl-3-aroylindoles have affinity for the cannabinoid brain (CB(1)) receptor. This has led to the development of over 100 cannabimimetic aminoalkylindoles, and the development of SAR for these compounds. Later work demonstrated that the aminoalkyl moiety was not necessary, and could be replaced by a four- to six-membered alkyl chain without loss of affinity. Investigation of these indoles led to the discovery of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
107
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(113 citation statements)
references
References 24 publications
4
107
1
1
Order By: Relevance
“…The profiles of AB-CHMINACA and FUBIMINA most closely matched those obtained previously with other synthetic cannabinoids, differing only quantitatively in their respective affinities, potencies, and efficacies. Similar to CP55,940 (present study) and other full dual CB 1 /CB 2 agonists (Huffman and Padgett, 2005), AB-CHMINACA and FUBIMINA displaced […”
supporting
confidence: 84%
See 1 more Smart Citation
“…The profiles of AB-CHMINACA and FUBIMINA most closely matched those obtained previously with other synthetic cannabinoids, differing only quantitatively in their respective affinities, potencies, and efficacies. Similar to CP55,940 (present study) and other full dual CB 1 /CB 2 agonists (Huffman and Padgett, 2005), AB-CHMINACA and FUBIMINA displaced […”
supporting
confidence: 84%
“…In the present study, the in vitro positive control CP55,940 showed low nM K i for both CB 1 and CB 2 receptors, similar to a number of indole and pyrrole-derived synthetic cannabinoids (Huffman and Padgett, 2005;Wiley et al, 2014a). Furthermore, it stimulated [ 35 S]GTPgS turnover with high potency and efficacy at both receptors, suggesting that CP55,940 would act as a potent CB 1 receptor agonist in vivo.…”
supporting
confidence: 66%
“…[1-naphthalenyl-(1-pentyl-1H-indol-3-yl]-methanone (JWH-018) and [1-(5-fluoropentyl)-1H-indol-3-yl]-1-naphthalenyl-methanone (AM2201) represent two common derivatives structurally characterized as aminoalkylindoles (Compton et al, 1992a,b;Atwood et al, 2010). These derivatives were first synthesized in the early 1990s to study the pharmacology of the cannabinoid type 1 (CB 1 ) receptor, the predominant G-protein-coupled receptor in the brain, and the cannabinoid type 2 (CB 2 ) receptor, located on immune cells (Huffman and Padgett, 2005;Mackie, 2008). Receptor binding studies have shown JWH-018 (Atwood et al, 2010;Brents et al, 2011) and other aminoalkylindoles to be high-affinity ligands (Ward et al, 1990;Thakur et al, 2005) at CB 1 and CB 2 receptors.…”
Section: Introductionmentioning
confidence: 99%
“…[7c,8] Many biologically active natural products and pharmaceutically important compounds contain the indene skeleton. [9] Meanwhile, indenes are also extensively used as ligands in organometallics [10a-c] and as functional materials.…”
Section: Introductionmentioning
confidence: 99%